Epidermotropic marginal zone lymphoma simulating mycosis fungoides†. (27th March 2013) - Lee, Bonnie A.; Jacobson, Mark; Seidel, Gregory
<x xml:space="preserve">Abstract</x> Cutaneous lymphomas can usually be distinguished by architectural features, where most atypical lichenoid infiltrates implicate cutaneous T‐cell lymphoma (CTCL). We report a case of an 80‐year‐old man who presented with asymptomatic golden brown patches and diffuse pink papules on his trunk, buttocks and hips. Biopsies revealed a lichenoid infiltrate and areas of epidermotropism. Although the overall architectural pattern was compatible with mycosis fungoides, the lymphocytes had a more monocytoid and plasmacytoid appearance, and there were interspersed mature plasma cells. Immunohistological studies revealed that the pleomorphic lymphocytes were predominantly B cells (CD20\+ and CD79a\+) with a subpopulation of smaller bland T cells (CD3\+). Moreover, the B‐cell immunophenotype was compatible with marginal zone differentiation (bcl‐2+, bcl‐6−, CD10− and CD5−) and showed a lambda light chain restriction, confirming monoclonality. These findings were diagnostic for cutaneous marginal zone B‐cell lymphoma (MZL) with epidermotropism an entity which has only been reported twice in the literature, once in the setting of primary cutaneous disease, and once as cutaneous involvement of systemic disease. This case illustrates a rare pattern of cutaneous MZL, and underscores the importance of immunophenotypic characterization of cutaneous lymphomas in order to prevent the misdiagnosis of a CTCL.